Scheme for the generation of a truncated endogenous murine leukaemia virus, the Fv-4 resistance gene - Inaguma, Yutaka; Yoshida, Takamasa; Ikeda, Hidetoshi (Journal of General Virology, 1992)
The Fv-4 resistance (Fv-4r ) gene is a truncated endogenous murine leukaemia virus (MuLV) containing a 3′ portion of pol, the entire env gene and the 3′ long terminal repeat. Env expression renders mice resistant to infection by ecotropic MuLVs, probably via receptor interference. Previous studies have suggested that the flanking cellular sequences are also important for Fv-4 env gene expression. To establish how the truncated retrovirus was generated and the nature of the cellular sequences involved, the Fv-4 susceptible (Fv-4s ) allele DNA was cloned, and its restriction map and nucleotide sequence were compared with those of the Fv-4r allele. A likely mechanism for generation of the truncated endogenous MuLV is suggested by the results; integration of a prototype MuLV provirus at a site within the Fv-4s allele about 6 to 8 kb downstream of a non-retroviral promoter region, followed by deletion of the 5′ half of the provirus, with an accompanying loss of only 7 or 10 bp of cellular flanking sequences. The deletion may have led to the expression of the Fv-4r env gene under control of the non-retroviral promoter.